Identifying drivers for user preference and acceptability of different hydro-alcoholic hand rub formulations. (November 2021) - Verwilghen, D.; Osiak, K.; Shaw, A.D.; Averay, K.; Kampf, G.; van Galen, G.
Summary: Background: In the current era, the importance of proper hand hygiene to reduce the transmission of infectious diseases has become difficult to debate. Yet, compliance rates remain low and are affected by many factors, amongst which is user acceptability of hand hygiene products. Aim: The present study aimed at investigating drivers of preference towards different hand hygiene formulations. Methods: Three different formulations (liquid, foam and gel) of the same brand were randomly and blindly evaluated by 54 participants based on the WHO Protocol for Evaluation of Tolerability and Acceptability of Alcohol-based Handrubs. Results: The majority (76%) of respondents indicated that the product formulation impacted their level of compliance with hand hygiene protocols. The preferred formulation was liquid, with 50% of participants ranking it as first choice. General product satisfaction, the product texture, the drying speed and the ease of application, were the statistically significant drivers for participants to rank a formulation as their first choice vs not ranking it as their first choice. Conclusions: When designing alcohol formulations and implementing hand hygiene protocols, understanding drivers of preference for formulations may enhance product user acceptability and therefore compliance with hand hygiene.